Tindak Tutur Ilokusi dalam Slogan Iklan Poster Produk Maybelline Green Edition Berbahasa Inggris - Diva Azmi; Siti Arinda Ersa Putri (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This research takes two advertisements for Maybelline Green Edition beauty products as the objects of analysis, as Maybelline is a globally recognized cosmetic brand. The product emphasizes an environmentally friendly label, reflecting consumer awareness of environmental issues. Through a pragmatic approach, this research identifies illocutionary speech acts used in the ad slogans based on Searle's theory of illocutionary speech act identification, namely assertive, commissive, directive, and declarative illocutions. Using a qualitative method, primary data is obtained from words, phrases, clauses, and sentences in the slogans of Maybelline Green Edition beauty product ads. The research shows that assertive illocution is the main strategy in influencing consumers of this product. The analysis results indicate that assertive illocutionary speech acts dominate both posters, with a focus on directly delivering product information. This research provides a profound understanding of the types of illocutionary speech acts used in Maybelline Green Edition beauty product ads, with findings that can serve as a reference for marketing practitioners to enhance the effectiveness of beauty product advertisements in an increasingly environmentally conscious market. Therefore, understanding illocutionary speech acts can form the foundation for more effective and relevant marketing strategies in the cosmetic industry.